Myocardial Architecture, Mechanics, and Fibrosis in Congenital Heart Disease - Ghonim, Sarah; Voges, Inga; Gatehouse, Peter D.; Keegan, Jennifer; Gatzoulis, Michael A.; Kilner, Philip J.; Babu-Narayan, Sonya V. (Frontiers in Cardiovascular Medicine, 2017)
Congenital heart disease (CHD) is the most common category of birth defect, affecting 1% of the population and requiring cardiovascular surgery in the first months of life in many patients. Due to advances in congenital cardiovascular surgery and patient management, most children with CHD now survive into adulthood. However, residual and postoperative defects are common resulting in abnormal hemodynamics which may interact further with scar formation related to surgical procedures. Cardiovascular magnetic resonance (CMR) has become an important diagnostic imaging modality in the long-term management of CHD patients. It is the gold standard technique to assess ventricular volumes and systolic function. Besides this, advanced CMR techniques, allow the acquisition of more detailed information about myocardial architecture, ventricular mechanics and fibrosis. The left and right ventricle have unique myocardial architecture that underpins their mechanics, however this becomes disorganised under conditions of volume and pressure overload. CMR diffusion tensor imaging (DTI) is able to interrogate non-invasively the principal alignments of microstructures in the left ventricular wall. Myocardial tissue tagging, (Displacement Encoding with Stimulated Echoes; DENSE) and feature tracking are CMR techniques that can be used to examine the deformation and strain of the myocardium in CHD, whereas 3D feature tracking can assess the twisting motion of the LV chamber. Late gadolinium enhancement (LGE) imaging and more recently T1 mapping can help in detecting fibrotic myocardial changes and evolve our understanding of the pathophysiology of CHD patients. This review not only gives an overview about available or emerging CMR techniques for assessing myocardial mechanics and fibrosis, it also describes their clinical value and how they can be used to detect abnormalities in myocardial architecture and mechanics in CHD patients.